PENGARUH KOMBINASI SARIPATI BUAH NANAS DAN PEPAYA TERHADAP KUALITAS FISIK DAGING ITIK PETELUR AFKIR - Anisa Ramadhani; Rr. Riyanti; Veronica Wanniatie; Dian Septinova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This research aimed to determine the effect of combination of pineapple and papaya fruit quintessence on pH, water holding capacity, and tenderness of meat of post production of laying duck. This research was conducted in December 2019 to January 2020 at Production and Reproduction of Livestock Laboratory, and Instrument Laboratory, Faculty of Agriculture University of Lampung. The materials of this research used were 20 pieces thigh meat of post production of laying duck. This research used a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatment were without marination of combination of pineapple and papaya fruit (P0), marination with 25% pineapple + 75% papaya (P1), marination with 50% pineapple + 50% papaya (P2), and marination with 75% pineapple + 25% papaya (P3). The variables observed were pH value, water holding capacity (WHC), and tenderness of laying duck meat. The data obtained were then analyzed by using variance analysis at 5% level, the result of which had significant effect were continued tested using the Least Significance Different (BNT). The results of the analysis of variance showed that the addition of laying duck meat with a combination of pineapple and papaya fruit quintessence did not effect (P>0,05) on physical quality of meat of post production of laying duck. Keywords: Laying duck meat, Papaya, Pineapple, Physical quality